2006
DOI: 10.1364/josab.23.000498
|View full text |Cite
|
Sign up to set email alerts
|

Nonmagnetic nanocomposites for optical and infrared negative-refractive-index media

Abstract: We develop an approach to use nanostructured plasmonic materials as a non-magnetic negative-refractive index system at optical and near-infrared frequencies. In contrast to conventional negative refraction materials, our design does not require periodicity and thus is highly tolerant to fabrication defects. Moreover, since the proposed materials are intrinsically non-magnetic, their performance is not limited to proximity of a resonance so that the resulting structure has relatively low loss. We develop the an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
166
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(169 citation statements)
references
References 40 publications
2
166
0
1
Order By: Relevance
“…An innovative approach, which makes use of arrays of high aspect ratio metallic wires, 17,18 has been theoretically suggested to mitigate the aforementioned drawbacks. The underlying mechanism for restoring evanescent waves in such metallic wires medium, is not based on resonances of materials parameters ͑i.e., there is no amplification machinery from excitation of surface waves at interfaces͒, but is rather based on the transport of evanescent waves when the medium exhibits a relatively flat equifrequency dispersion characteristics.…”
mentioning
confidence: 99%
“…An innovative approach, which makes use of arrays of high aspect ratio metallic wires, 17,18 has been theoretically suggested to mitigate the aforementioned drawbacks. The underlying mechanism for restoring evanescent waves in such metallic wires medium, is not based on resonances of materials parameters ͑i.e., there is no amplification machinery from excitation of surface waves at interfaces͒, but is rather based on the transport of evanescent waves when the medium exhibits a relatively flat equifrequency dispersion characteristics.…”
mentioning
confidence: 99%
“…Such materials were carefully studied by different groups [51][52][53][54][55][56][57][58][59][60][61][62][63]. It is shown that indefinite media can have negative group refraction, backward-wave effect, and partial focusing.…”
Section: The Methods To Reduce the Losses Of Optical Metamaterialsmentioning
confidence: 99%
“…But the double resonance scheme also causes large resonance losses and technical difficulties in design and fabrication. In addition to negative index materials, both theoretical and experimental studies show the properties of negative refraction and subwavelength imaging can also occur in some uniaxially anisotropic media, which can have lower losses and be easier to fabricate [51][52][53][54][55][56][57][58][59][60][61].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations